Asymptomatic bacteriuria in pregnancy screening, risk factors, diagnosis and treatment - Meshram, Pallavi S.; Kubde, Ashish R.; Kothalkar, Vijayalakshmi S.; B. Giri, Avinash (International Journal of Research in Medical Sciences, 2023)
Background: Asymptomatic bacteriuria is a frequent pregnancy issue that, if left untreated, increases the risk of premature birth and pyelonephritis. Urine culture is the basis for the diagnosis. In the current study, 200 pregnant women are examined for severe asymptomatic bacteriuria to gain insight into its frequency in emerging nations, to re-evaluate some predisposing factors, and to test for the susceptibility of specific aetiological agents. The purpose of this study was to assess the prevalence of asymptomatic bacteriuria in pregnant women as well as to isolate, characterise, and establish the pathogens antibiotic susceptibility patterns. Methods: 200 pregnant women with asymptomatic bacteriuria are included in the study. By using traditional techniques, isolates were located, and their antibiotic susceptibility patterns were established. Results: Significant bacteriuria was detected in 102 individuals (51%) in total. The three most efficient antibiotics against the urine isolates were determined to be Piperacillin-Tazobactam, Amikacin, and Nitrofurantion. Escherichia coli was the most prevalent bacterium, followed by Klebsiella pneumoniae. Conclusions: In the group under study, prenatal patients frequently have asymptomatic bacteriuria. All prenatal patients should have routine urine cultural testing to detect any undetected infections. This action will significantly lessen pregnancy-related maternal and obstetric problems.